(untitled) (Veterinary Science, 2021)
The objective of this investigation was to study the supplementation of injectable trace minerals (ITM), based on Cu, Zn, Mn, and Se on reproductive performance of dairy cows from Torreon, Mexico, a geographical region characterized by a semi-desertic climate. The study consisted of 2 field trials. Trial 1 compared the application of 2 doses of ITM during the dry period (at dry-off and at prepartum) (n= 75) with a control group (n=79). Trial 2 compared the application of 1 dose of ITM at 35 d postpartum (n=258) with a control group (n=258). In both trials, conception rate at first service (CRFS) and days to conception were evaluated. In Trial 1, CRFS was not different between groups, but calving to conception interval tended to be shorter in 10 days in the treated than the control group (P=0.14). In trial 2, CRFS was not different between groups either, but time to pregnancy was significantly 14 days earlier than the control group (P ≤ 0.05). It is concluded that although CRFS was similar between groups, the application of an ITM reduced the time to pregnancy in treated than the control groups, which have a great impact on herd’s fertility and profit.